PENINGKATAN HASIL BELAJAR PENYAJIAN DATA MENGGUNAKAN MODEL PROJECT BASED LEARNING (PjBL) PADA MURID KELAS V SDN DUKUH KUPANG II/489 SURABAYA - Tollanda Dhesika Aulia; Tiara Zalza Nabilah; Muhammad Hafidz Amaluddin; Wahyu Susiloningsih; Menik Rupiati; Ganda Riswanto (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research was motivated by the low mathematics learning outcomes of Grade V students at SDN Dukuh Kupang II/489 Surabaya on the topic of data presentation. The aim of this research was to improve student learning outcomes through the implementation of the Project Based Learning (PjBL) model on bar chart data presentation material. This Classroom Action Research (CAR) was conducted in two cycles, each consisting of planning, implementation, observation, and reflection stages. The subjects were 28 Grade V students in the academic year 2025/2026. Data collection techniques included tests, observations, and documentation. Data were analyzed using quantitative and qualitative descriptive analysis. The results showed that the application of the PjBL model effectively improved student learning outcomes. Classical learning mastery increased from 50% (pre-cycle), to 71% (Cycle I), and reached 89% (Cycle II), exceeding the research target of 80%. The class average score improved from 62.5 (pre-cycle) to 74.3 (Cycle I) and 83.7 (Cycle II). Student activity in the dimensions of critical thinking, creativity, collaboration, and communication also improved from the Developing/Proficient category in Cycle I to the Expert category in Cycle II. It is concluded that the Project Based Learning (PjBL) model can significantly improve the learning outcomes of Grade V students on bar chart data presentation material.